Apical debris extrusion of single-file systems in curved canals - Ecehan Hazar; Olcay Özdemir; Mustafa Murat Koçak; Baran Can Sağlam; Sibel Koçak (Wolters Kluwer Medknow Publications, 2021)
Objectives: The aim of this study was to compare the apical debris extrusion after using three different single-file systems. Materials and Methods: Mesial roots with curved canals of extracted mandibular molar teeth were randomly divided into three experimental groups according to preparation techniques: the XP-endo Shaper, WaveOne Gold, and One Curve. Previously weighed Eppendorf tubes were used to collect the debris which was placed in a 35°C hot water bath. The weight of the empty tube was subtracted from the final weight after instrumentation and recorded as the amount of extruded debris. The data were analyzed using the Kruskal-Wallis test at a 5% level of significance and compared all groups. Results: XP-endo Shaper presented less debris extrusion than WaveOne Gold and One Curve (P < 0.05). There was no significant difference between the WaveOne Gold and the One Curve files (P > 0.05). Conclusions: All the tested file systems caused debris extrusion. XP-endo Shaper caused less debris extrusion than WaveOne Gold and One Curve files.